Peranan Alat Navigasi di Kapal Untuk Meningkatkan Keselamatan Pelayaran di Atas Kapal - Yasin Muhammad Syibli; Dedi Nuryaman (Dinamika Bahari, 2021)
The guard rules that have been set by Collision Regulation 1972, STCW 1978 as amended in 2010 Regulation II / 1, all ships are obliged to carry out the guard duty without exception. As for the implementation, the duty officer must ensure that 1) All visual early warnings are taking place on the existing situation, including the presence of ships and signs from the land. 2) Continuous observation and bearing of approaching ships. 3) Identifying ships and land lights. 4) Checking the direction of the steering wheel and commanded steering signals. 5) Radar observation and echo sounder. 6) Observation of weather changes, especially visibility. This research uses a qualitative approach with descriptive delivery. The purpose of this study is to describe the role of navigation tools in increasing the level of shipping safety. With the results of this study, where an officer must optimize the operation and maintenance of navigation devices in order to carry out a proper observation. The use of navigation tools such as binoculars, radar, Automatic Identification System (AIS), and Electronic Charts Display and Identification System (ECDIS) is very helpful in optimizing existing observations. So improving skills in guard duty, especially in terms of making observations, must be as optimal as possible to take advantage of the help of navigation tools. Because observation is very important in order to avoid the danger of collision and achieve safety in shipping.